The Use of Monoclonal Antibodies in the Treatment of Alzheimer Disease - Moradi-Sardareh, Hemen; Moradi, Maryam; Bordbar, Elham; Malekpour, Mohammadreza; Bagheri, Sara; Nakhodazadeh, Nasrin; Rahbar, Shahin; Farhadian Asgarabadi, Javad (Asian Pacific Journal of Cancer Biology, 2016)
Background and objective: Antibody molecules have similar structure but variable binding sites to antigen. Human antibodies are achieved by transgenic mouse technology or phage display. Antibodies are used for the treatment of different diseases. Alzheimer is a cow disease with a delayed onset overpresenting in adults in their 70s to 90s. This disease is the leading cause of central nervous system (CNS) degeneration during 7 to 15 years in the aging population. Several hypotheses have offered monoclonal antibodies action mechanism in relation to amyloid cleaning at Alzheimer disease. According to this mechanism, the appropriate antibody passes blood-brain barrier, enters into brain, and binds to amyloid to launch its phagocytosis activity in microglia and/or macrophage/monocytes infiltrating. The present study aimed to review antibody structure and the use of different antibodies for the treatment of Alzheimer disease.